Facções criminosas, policiamento e democracia: disputas de ordens em territórios faccionados - Freitas, José Messias Mendes (2022)
The State limits the human experience of living freedom without the existence of an external regulator, in the sense that everything that is mandatory for man has its origin outside of him. Then, being associated with some group of people is the most binding of all obligations. Thus, just as the family is endowed with associative capacity, tying children to their descendants, political societies link clusters of secondary societies, whose eminence materializes in the figure of the State. The State a rational and centralizing actor is characterized by its ability to maintain order, a form of domination also present in criminal factions. All domination has an asymmetrical nature; it is based on a relationship of inequality. Therefore, the use of violence is not enough to give it long-term support, requiring ideological resources, a kind of consent that leads to accepting as fair and natural the asymmetry of domination. Criminal factions use these same resources by two different categories: immaterial and real. They reconcile the threat of force with the fascination of recognition, protection and solidarity. In this universe of transcendence, the desire to belong to a criminal factions as an institution that references conduct, the role of the police becomes incredibly complex and its actions have a significant impact on the quality of democracy and consequently on the ability of factions to co-opt. Since citizenship is the mythical league that justifies submission to the State, the more public security institutions adopt processes that strengthen citizenship, the less criminal factions find spaces to exercise their criminal governance. This sensitive relationship, with poorly defined contours, between the use of State force and the promotion of citizenship, we call Staticity. It contains the ideal of equality, as a constitutive element of democracy, so that the relationship between policing and criminal factions requires discussion beyond the simplism of the fight of good against evil. Neglecting the attribute of citizenship in the dispute between orders, waged between the State and criminal organization, generates fertile territories, spaces where they continue to attract their members, mobilized by the fetish of reverse citizenship.